Getting it done : a guide for government executives - Abramson, Mark A., 1947- (IBM Center for the Business of Government., 2016)
Getting It Done was written for those who have answered the call to public service. Now, in this 2017 edition, the editors of IBM's Center for The Business of Government series have assembled a comprehensive guide to navigating the current environment of government, and what government leaders ought to know to survive and thrive with respect to the ways it's evolved over the years. Concise analyses of the roles and responsibilities of those involved in any political decision accompany informative and instructional chapters, each highlighting a key step any public servant must take to ensure th.